Exploring older migrants’ meaning-making of ‘happiness’: “The main thing is health. Young people might say otherwise.” - Micheline Phlix; Jan Vanrie; Ann Petermans; An-Sofie Smetcoren (International Journal of Qualitative Studies on Health & Well-Being)
Purpose As our ageing population is growing and diversifying, it is important to gain insight into the well-being of older migrants. However, the meanings of happiness can vary cross-culturally. Therefore, prior to exploring older migrants’ happiness, their meaning-making of “happiness” should be explored. This way, cultural or individual variations can be considered when analysing older migrants’ happiness. Not only migration background but also age could influence the meaning of well-being. For example, the meaning of well-being can change as people grow older. Therefore, both migration background and age are considered in exploring older migrants’ meaning-making of happiness. Methods To do so, in-depth interviews with older migrants (n = 22) from various ethnicities were conducted in which their meaning-making of happiness was questioned via a semi-structured interview guide. Results After analysing the results via thematic analysis, three overarching themes are discussed: (1) happiness associations, (2) happiness-pursuing strategies, and (3) happiness obstructions. The analysis then further focuses on the role of migration background and ageing on the meaning-making of happiness. Conclusions Participants’ meaning-making of happiness seems strongly imbued with age-related references. On the contrary, the impact of migration background is rather limited. To explain this difference, the value of incorporating participants’ life course experiences emerged.